Analysis of LQ45 and ESG Stock Return Volatility on the Indonesia Stock Exchange - Umi Indah Hapsari; Hermanto Siregar; Tanti Novianti; Nimmi Zulbainarni (Institut Bisnis dan Informatika Kesatuan, 2025)
The Covid-19 pandemic created significant turmoil in global financial markets, including the Indonesia Stock Exchange, where liquidity and stability were severely disrupted by widespread panic and economic uncertainty. Investors faced heightened risks as stock prices fluctuated sharply in response to rapidly changing market conditions. This study examines the impact of the Covid-19 pandemic on stock volatility and performance by comparing conventional liquid stocks from the LQ45 index with sustainable stocks from the ESG (Environmental, Social, and Governance) indices. Using daily closing prices from January 1, 2016, to December 31, 2023, the analysis employs the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model to capture volatility patterns. The findings reveal that LQ45 stocks consistently exhibit higher volatility than ESG stocks, yet deliver superior returns across all periods. Conversely, ESG stocks show greater resilience during the pandemic, maintaining relatively stable performance despite lower returns compared to LQ45. These results underscore the value of incorporating sustainable investment strategies, particularly when combined with liquidity considerations, as a means to balance risk and return while enhancing portfolio stability during periods of market uncertainty.